Experimental Study on the Creep Behavior of Red Sandstone under Low Temperatures. (9th October 2019) - Song, Yongjun; Zhang, Leitao; Yang, Huimin; Ren, Jianxi; Che, Yongxin
Abstract : In cold regions, the deformation characteristics and long-term mechanical properties of rocks under low-temperature conditions are considerably different from those in other regions. To study the deformation characteristics and long-term mechanical properties of rocks in a low-temperature environment and the effect of different temperatures, we perform a multilevel loading-unloading uniaxial creep test on red sandstone samples and obtain the creep curves at different temperatures (20°C, −10°C, and −20°C). The results demonstrate that the total strain at each temperature can be divided into instantaneous and creep strains; the instantaneous strain includes instantaneous elastic and plastic strains, and the creep strain includes viscoelastic and viscoplastic strains. Temperature has a significant effect on the deformation properties of red sandstone. A decrease in temperature reduces the instantaneous and creep deformations of the rocks at all levels of stress. In addition, a decrease in temperature exponentially attenuates the total creep and viscoplastic strains of the rocks. 0°C is a critical point for the reduction of the total creep and viscoplastic strains of the rocks. When the temperature is greater than 0°C, the total creep and viscoplastic strains of the rocks decrease rapidly and linearly with decrease in temperature; however, when the temperature is less than 0°C, the decrease in the total creep and viscoplastic strains of the rocks is slow. The steady-state creep rate of the rock samples decreases with decrease in temperature, whereas the creep duration increases with decrease in temperature, especially in the case of the accelerated creep stage. The accelerated creep durations of the rock samples S4 (20°C) and S7 (–10°C) are 0.07 h and 0.23 h, respectively.